Assessment of Plumage and Integument Condition in Dual-Purpose Breeds and Conventional Layers - Giersberg, Mona Franziska (Animals (Basel), 2017)
SIMPLE SUMMARY: Behavioural problems, such as injurious pecking, are major welfare concerns in laying hen husbandry. To take adequate measures at the right time, useful information about the occurrence of these problems in a flock can be obtained by examining the hens for feather loss and skin injuries. Although feather loss and injuries can also result from mechanical abrasion or health issues, they provide strong evidence of behavioural problems in a flock, particularly when observed on the back and the tail of the animals. In our study, the behaviour of two genetic strains of laying hens (conventional layers and dual-purpose breeds) was evaluated by means of two different methods for assessing the feathers and the skin on distinct body parts of the animals. One method was a mere visual inspection of the flocks, whereas the other included the capture and handling of individual hens. Damaging behaviour, which resulted in severe feather loss and skin injuries, only occurred in the conventional layers. Both of the methods provided similar results for feather loss and injuries for most of the tested body regions and weeks. Therefore, the mere visual method was sufficient to detect injurious behaviour in laying hens. ABSTRACT: The assessment of plumage and integument condition in laying hens provides useful information about the occurrence of feather pecking and cannibalism. Although feather loss and skin injuries can result from mechanical abrasion or clinical diseases, they are valid animal-based indicators for behavioural disorders. This particularly applies to damage on the back and tail region of the hens. The aim was to evaluate the behaviour of dual-purpose breeds (Lohmann Dual, LD) and conventional layer hybrids (Lohmann Brown plus, LB+), and to compare a mere visual assessment (Visual Scoring, VSc), with a method involving the handling of individual animals (Hands-on Scoring, HSc). During weekly VSc, the hens’ plumage and integument were scored on five body parts. HSc was carried out on seven study days applying the same scoring scale as for VSc. In LB+ hens, minor plumage damage started at 25 weeks and increased to the 71st week. With 99.5% of LB+ showing feather loss to a different extent, the back was the most severely affected body part. In contrast, only between 4.5% and 7% of LD showed minor feather loss at the end of the study. Integument damage reached a peak, with 6% affected LB+ in week 66. Injuries were found only sporadically in LD hens. Spearman’s rho for the comparison of plumages scores given in VSc and HSc was >0.90 (p < 0.01) in both hybrids for most of the tested body regions and weeks, except for the breast/belly region. However, VSc and HSc were equally valid for detecting skin injuries of all of the body regions (r(s) > 0.86, p < 0.01). Damaging behaviour only occurred in the LB+ flocks, though both of the genetic strains were kept under the same conditions. The visual scoring method was suitable for detecting both plumage and integument damage.